Rich oleocanthal and oleacein extra virgin olive oil and inflammatory and antioxidant status in people with obesity and prediabetes. The APRIL study: A randomised, controlled crossover study - Ruiz-García, Ignacio; Ortiz-Flores, Rodolfo; Badía, Rocío; García-Borrego, Aranzazu; García-Fernández, María Inmaculada; Lara, Estrella; Martín-Montañez, Elisa; García Serrano, Sara; Valdés, Sergio; Gonzalo, Montserrat; Tapia Guerrero, María José; Fernández-García, José Carlos; et al. (Elsevier, 2023)
Background: Oleocanthal and oleacein are olive oil phenolic compounds with well known anti inflammatory and anti-oxidant properties. The main evidence, however, is provided by experimental studies. Few human studies have examined the health benefits of olive oils rich in these biophenols. Our aim was to assess the health properties of rich oleocanthal and oleacein extra virgin olive oil (EVOO), compared to those of common olive oil (OO), in people with prediabetes and obesity. Methods: Randomised, double-blind, crossover trial done in people aged 40e65 years with obesity (BMI 30e40 kg/m2 ) and prediabetes (HbA1c 5.7e6.4%). The intervention consisted in substituting for 1 month the oil used for food, both raw and cooked, by EVOO or OO. No changes in diet or physical activity were recommended. The primary outcome was the inflammatory status. Secondary outcomes were the oxidative status, body weight, glucose handling and lipid profile. An ANCOVA model adjusted for age, sex and treatment administration sequence was used for the statistical analysis. Results: A total of 91 patients were enrolled (33 men and 58 women) and finished the trial. A decrease in interferon-g was observed after EVOO treatment, reaching inter-treatment differences (P ¼ 0.041). Total antioxidant status increased and lipid and organic peroxides decreased after EVOO treatment, the changes reaching significance compared to OO treatment (P < 0.05). Decreases in weight, BMI and blood glucose (p < 0.05) were found after treatment with EVOO and not with OO. Conclusions: Treatment with EVOO rich in oleocanthal and oleacein differentially improved oxidative and inflammatory status in people with obesity and prediabetes.
Keywords: Fenoles; Diabetes - Aspectos nutricionales; Oleocanthal; Oleacein; Olive oil; Obesity; Prediabetes; Inflammation